Change in Soil and Forest Floor Carbon after Shelterwood Harvests in a New England Oak-Hardwood Forest, USA. (5th May 2014) - Warren, Kayanna L.; Ashton, Mark S.
Abstract : There has been effort worldwide to quantify how much carbon forests contain in order to designate appropriate offset credits to forest carbon climate mitigation. Carbon pools on or immediately below the soil surface are understood to be very active in response to environmental change but are not well understood. Our study focused on the effects of shelterwood regeneration harvests in New England on the carbon stored in litter, woody debris, and surface soil carbon. Results demonstrate significant difference in surface (0–10 cm) soil carbon between control (nonharvested) and harvested sites, with higher carbon percentage on control sites. Results showed a significant difference in coarse woody debris with higher amounts of carbon per area on harvested sites. No significant difference in litter mass was recorded between harvested and control sites. When coarse woody debris and litter are included with soil carbon, total carbon did not have a significant decline over 20 years following shelterwood treatment to the forest to secure regeneration, but there was considerable variability among sites. When taking all surface soil carbon measurements together, our results suggest that for accounting purposes the measurement of below-ground carbon after shelterwood harvests is not necessary for the southern New England region.